Replication of Venezuelan Equine Encephalomyelitis Virus In Vitro: II. Viral Growth Response to Selected Nutritional Additives in Suspension Cultures - Hearn, H. J. (1971)
An attempt was made to identify nutritional additives that influence the replication of Venezuelan equine encephalomyelitis virus in suspension cultures grown in a defined serum-free medium. Proline, serine, and choline enhanced titers of the virulent PES strain; the progeny population, however, possessed a virulence character that was somewhat different from that of the PES inocula. These nutritional supplements did not appreciably influence the titers of the attenuated 9t and 20t viral strains. When both the PES and 20t strains were employed as a mixed inoculum in culture, the presence of the latter strain appeared to interfere with the growth of the PES strain and reduced its response to the medium supplements.